2007
DOI: 10.1016/j.jorganchem.2007.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of [Re2(CO)8(MeCN)2] with thiazoles: Hydrido bridged dirhenium compounds bearing thiazoles in different coordination modes

Abstract: Reactions of the labile compound [Re 2 (CO) 8 (MeCN) 2 ] with thiazole and 4-methylthiazole in refluxing benzene afforded the new compounds [Re 2 (CO) 7 {l-2,3-g 2 -C 3 H(R)NS}{g 1 -NC 3 H 2 (4-R)S}(l-H)] (1, R = H; 2, R = CH 3 ), [Re 2 (CO) 6 {l-2,3-g 2 -C 3 H(R)NS}{g 1 -NC 3 H 2 (4-R)S} 2 (l-H)] (3, R = H; 4, R = CH 3 ) and fac-[Re(CO) 3 (Cl){g 1 -NC 3 H 2 (4-R)S} 2 ] (5, R = H; 6, R = CH 3 ). Compounds 1 and 2 contain two rhenium atoms, one bridging thiazolide ligand, coordinated through the C(2) and N atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The infrared spectrum display three bands in the carbonyl stretching region indicating the fac arrangement of the carbonyls, similar to those observed for fac-[Re(CO) 3 L 2 X] type compounds [24][25][26][27][28]. In addition to the usual phenyl and naphthyl Re 2 (CO) 8 proton resonances in the aromatic region d 7.92-6.50, the 1 H NMR spectrum shows a doublet of doublets at d 4.93 (integrating to 1H) assigned to the PH proton of the diphenylphosphine ligand.…”
Section: Formation Of Mononuclear Rhenium Complexes By C-p and C-h Bosupporting
confidence: 75%
See 2 more Smart Citations
“…The infrared spectrum display three bands in the carbonyl stretching region indicating the fac arrangement of the carbonyls, similar to those observed for fac-[Re(CO) 3 L 2 X] type compounds [24][25][26][27][28]. In addition to the usual phenyl and naphthyl Re 2 (CO) 8 proton resonances in the aromatic region d 7.92-6.50, the 1 H NMR spectrum shows a doublet of doublets at d 4.93 (integrating to 1H) assigned to the PH proton of the diphenylphosphine ligand.…”
Section: Formation Of Mononuclear Rhenium Complexes By C-p and C-h Bosupporting
confidence: 75%
“…The coordination geometry of the Re atom can be described as a distorted octahedron with three carbonyl ligands arranged in a facial fashion. The distortion from octahedral coordination geometry is evident from reduction of the P-Re-P angle from 90°in the idealized polyhedron to 82.50 (11) [25]. The reason for lengthening the other two Re-CO bond distances is probably due the trans effect of the two P atoms of the chelating dppn ligand.…”
Section: Formation Of Mononuclear Rhenium Complexes By C-p and C-h Bomentioning
confidence: 99%
See 1 more Smart Citation
“…To gain insight into the reactivity of secondary aliphatic heterocyclic amines toward rhenium carbonyl complexes, we have investigated the reaction of morpholine with [Re 2 (CO) 8 (MeCN) 2 ] to isolating the g 1 -coordinated compound [Re 2 (CO) 8 . Both compounds 2 and 3 have been characterized by elemental analysis, IR, 1 H NMR and mass spectral data together with single crystal X-ray diffraction analysis for 3.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and reactivity of the dirheniumpyridyl compound [Re 2 (CO) 8 (l-g 2 -C 5 H 4 N)-(l-H)] were investigated by Brown and co-workers in 1982 [7]. Arce et al [4] reported the bipyridyldirhenium complexes [Re 2 (CO) 8 (l-g 3 -C 12 H 10 N 2 )], [Re 2 (CO) 7 (l-g 3 -C 12 H 9 N 2 )-(l-H)], [Re 2 (CO) 6 (l-g 4 -C 12 H 9 N 2 )(l-H)], [Re 2 (CO) 8 (l-g 4 -C 12 H 10 N 2 )] and [Re 2 (CO) 6 (l-g 6 -C 24 8 (MeCN) 2 ] with thiazole and 4-methylthiazole [8].…”
Section: Introductionmentioning
confidence: 99%